2021
DOI: 10.5194/essd-13-4847-2021
|View full text |Cite
|
Sign up to set email alerts
|

Mineral, thermal and deep groundwater of Hesse, Germany

Abstract: Abstract. The composition of mineral, thermal or deep groundwaters is of interest for several geotechnical applications, such as drinking-water supply, spas or geothermal energy. Verified and reliable knowledge of temperature, pH, hydrochemical composition and other parameters is crucial to extract fluids with as few technical problems as possible and exploit groundwater reservoirs economically and environmentally sustainably. However, at sites where empirical data are lacking, the correct prediction of fluid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the Zechstein unit, the parameterization of salinity is complicated, caused by highly heterogeneous lithologies from dolomite to pure salt (Bär 2012), which cannot be incorporated accurately in a regional scale model. However, low salinities of 34 g l −1 [mean values from the new data base by Schäffer et al (2020Schäffer et al ( , 2021] and very high salinities of 443 g l −1 [mean values for Hesse by Ludwig (2013)] were both tested as endmembers for the fluid composition and properties. The resulting HIP calculated with different salinity varies only up to 2%, therefore it can be concluded that the exact knowledge of the salinity of the geothermal reservoir has a subordinate relevance for regional predictions of HIP compared to thickness, temperature or porosity.…”
Section: Discussionmentioning
confidence: 99%
“…In the Zechstein unit, the parameterization of salinity is complicated, caused by highly heterogeneous lithologies from dolomite to pure salt (Bär 2012), which cannot be incorporated accurately in a regional scale model. However, low salinities of 34 g l −1 [mean values from the new data base by Schäffer et al (2020Schäffer et al ( , 2021] and very high salinities of 443 g l −1 [mean values for Hesse by Ludwig (2013)] were both tested as endmembers for the fluid composition and properties. The resulting HIP calculated with different salinity varies only up to 2%, therefore it can be concluded that the exact knowledge of the salinity of the geothermal reservoir has a subordinate relevance for regional predictions of HIP compared to thickness, temperature or porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Shahri [ 20 ] states that “the thermal and mineral waters of Mosul are sodium chloride and sulfated.” Hashim, in 2020, [ 21 ] in his study of the chemical and toxicological evaluation of lithium, found 15.95 mg/L of said element in the thermal water. Hashim [ 21 ] affirms that the thermal water of Mosul presents sodium 1682.31 mg/L, chloride 1962.31 mg/L, and sulfate 861.91 mg/L; however, in the study that was carried out, sodium 1869.63 mg/L, sulfate 7796.30 mg/L, potassium 75.06 mg/L, chloride 1610.62 mg/L, and by concerning previous studies, sodium concentrations increased by 27% and potassium by 24% over time. However, the concentrations of sulfates decreased by 11% and chlorides by 20%, decreasing as time went by, probably due to the degradation of volcanic rocks, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The spa has been using acidolous thermal brine from springs and boreholes for over 175 years (Hanna, 1986, Hansmann & Noll, 1987. The oldest available water analysis dates back to 1877 from the Barbarbossaquelle (Himstedt et al, 1907), giving a nearly 150-year series of measurements (Schäffer et al, 2021b). Over this time, springs and increases with depth and due to different aquifer levels (Schäffer et al, 2018), illustrated, for example, by the analyses of Trinksprudel wells 1 and 2 (Figure 2a).…”
Section: Evaluation Of Rise and Dilution Of Acidulous Thermal Brinementioning
confidence: 99%